Pemetaan Kemiringan Lereng Menggunakan Software Geographic Information System Pada Sub DAS Way Pubian - Setyanugraha, Tegar; Romdania, Yuda; Herison, Ahmad; Zakaria, Ahmad (Universitas Lampung, 2023)
Land use utilization in a watershed must pay attention to the slope. The slope that will be analyzed is the slope of the Way Pubian Subwatershed, Way Seputih Watershed, Lampung Province. Over time, population growth will increase in the Way Pubian Subwatershed area resulting in land use change which is an important trigger factor for landslides. Perhaps slope mapping has been done in many places, but for the Way Pubian Subwatershed area it has never been done. So it is important to conduct slope mapping in the Way Pubian Subwatershed. The purpose of the study was to conduct slope mapping and its classification using ArcGIS. Based on the results of the analysis with ArcGIS obtained slope map in Way Pubian Subwatershed with five classifications namely flat (0-8%), ramps (8-15%), rather steep (15-25%), steep (25-45%), and very steep (>45%). Way Pubian Subwatershed has an area of 11,562.8762 Ha where 3,026.7852 Ha (26.1767%) is the classification of 25-45% slope class (Steep) which is the largest compared to the area of other classification classes. In the classification class flat (0-8%), ramps (8-15%) and rather steep (15-25%) do not have too much difference. While the very steep classification class (>45%) is the area with the least area. The conclusion is that the slope map is obtained with the largest classification of slope is in the steep class.